Comparative quality and volatilomic characterisation of unwashed mince, surimi, and pH-shift-processed protein isolates from farm-raised hybrid catfish (Clarias macrocephalus × Clarias gariepinus). (1st December 2021) - Phetsang, Hatairad; Panpipat, Worawan; Undeland, Ingrid; Panya, Atikorn; Phonsatta, Natthaporn; Chaijan, Manat
Graphical abstract: Highlights: Alkali pH-shift (Alk) removed most geosmin, 2-MIB, lipids and myoglobin. Alk minimized accumulation of unpleasant volatiles with better gelling properties. Acid pH-shift hastened lipid oxidation and evolution of undesirable volatiles. Surimi process was unsuitable for hybrid catfish due to the lowest gelling ability. Abstract: Earthy off-odour in farm-raised freshwater fish is considered a quality defect. This study aimed to investigate the potential of pH-shift processing to remove off-odours from farm-raised hybrid catfish while at the same time documenting de-novo formation of other volatile compounds. In comparison with crude mince and conventional surimi, the alkali pH-shift process gave larger reductions in geosmin, 2-methylisoborneol, undesirable volatile compounds (e.g. hexanal, ( E )-2-nonenal, ( E )-2-heptenal, 2-butanone, and hexadecane), lipids, myoglobin, total volatile basic nitrogen, and TCA-soluble peptides (p < 0.05). The acid-produced protein isolate showed the highest TBARS and processing-induced evolution of the following volatiles: octanal, nonanal, decanal, 2-butyl-2-octenal, pentadecanal, 1-hexanol, 1-octanol, 1-octen-3-ol, and 2, 3-octanediol (p < 0.05). Alkali-aided process provided better overall gelling characteristics (i.e. breaking force, deformation, and texture profile) and gave lower fishy, earthy, and rancid off-odour scores (p < 0.05). Thus, alkali pH-shift process can be used to isolate gel-forming proteins from hybrid catfish while minimizing the accumulation of undesirable volatile compounds.